Ethnic Drift and White Flight: A Gravity Model of Neighborhood Formation - Jessie Bakens; Raymond Florax; Peter Mulder (Tinbergen Institute, 2016)
Ethnicity has become an increasingly important factor in neighborhood formation in many developed economies. We specify a gravity model for neighborhoods to assess the role of ethnicity in intra-urban residential relocations. Migration patterns of different ethnic groups are hypothesized to depend on bilateral socioeconomic, demographic and ethnic differences between origin and destination neighborhoods. We account for heterogeneous and interdependent location preferences of natives and several immigrant groups. In addition, we incorporate friction measures of ethnic population shares and a diversity indicator to allow for nonlinear and asymmetric effects of the population composition on ethnic sorting and spatial clustering. We utilize a unique micro data set of place-to-place migrants across neighborhoods in the urban agglomerations of Amsterdam and The Hague, in The Netherlands. Our results provide evidence of ethnic drift leading to clustering of ethnic minority groups and "white flight" of native Dutch residents. Taken together, our findings suggest a preference for living among people of one's own ethnic group, but in a sufficiently diverse neighborhood. We discuss ways to extend and apply our gravity approach to further analyze intra-urban residential relocation flows.
Keywords: C21; F22; J15; J61; R23; 330; neighborhood formation; ethnicity; diversity; immigrants; gravity model